Giju Bhai Badheka: On Being a Primar Giju Bhai Badheka: On Being a Primary Teacher - Jass, Harpreet (THE PRIMARY TEACHER, 2009)
Experiments of great thinkers and educationists can act as beacon light to guide our thoughts. One such thinker, teacher and educationist we had in India is Giju Bhai Badheka. He lived and worked in Gujarat. The purpose of this article is to look into his thoughts and ideas as an answer to present challenges of primary education in India. The strength of his thoughts lies in his simple description of situation or the problems he faces and then with equal honesty he tries to find the answer to it. He uses common sense to see what works with children to teach them concepts. He also tries to understand the underlying concept of the topic to be taught. His fight is against the system and those notions of learning that fail children or do not allow children to become good learners. Teaching is very challenging and a serious job according to him and requires sincerity on part of the teacher to see what works out the best.